Evaluation of Biomedical Laboratory Performance Optimisation Using the DEA Method - Lamovšek Nejc; Klun Maja (Sciendo, 2020)
The Slovenian Resolution on the National Healthcare Plan notes that the country's medical laboratory activities are fragmented, which may result in cost-inefficiency and a reduction in the quality of the services provided. Defining the efficiency of laboratory service providers can therefore help us to pursue the objectives of the Resolution, i.e. to consolidate and integrate laboratory activities.